2020
DOI: 10.1111/faf.12496
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of gas bubble trauma in fish

Abstract: There is currently a worldwide proliferation of dams, with 59 000 hydroelectric dams over 15 m high registered with the International Commission On Large Dams (2018). Furthermore, there are an additional 3,700 hydroelectric dams over 1 megawatt (MW) planned or under construction as of 2015 (Zarfl, Lumsdon, Berlekamp, Tydecks, & Tockner, 2015). Once these dams are constructed, the number of large, free-flowing rivers worldwide will be further reduced by 21% (Zarfl et al., 2015). These numbers do not account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 44 publications
1
62
0
Order By: Relevance
“…Thus, if moderate levels of O 2 supplementation are used in fish rearing systems, for example to avoid hypoxia at increased stocking densities, care should be taken to avoid hyperbaric total gas pressures and unintended harmful impacts. Interestingly, a recent meta‐analysis of gas bubble disease in fish found that a higher O 2 to nitrogen ratio under conditions of increased total gas pressure actually improves resilience to gas bubble trauma (Pleizier et al., 2020). This is because O 2 , as opposed to nitrogen, is consumed by aerobic metabolism, which leads to a lower total gas pressure in the tissues than would otherwise be experienced at a particular level of increased total gas pressure (Pleizier et al., 2020).…”
Section: The Influence Of Hyperoxia On Growth Performance and Gas Bubmentioning
confidence: 99%
“…Thus, if moderate levels of O 2 supplementation are used in fish rearing systems, for example to avoid hypoxia at increased stocking densities, care should be taken to avoid hyperbaric total gas pressures and unintended harmful impacts. Interestingly, a recent meta‐analysis of gas bubble disease in fish found that a higher O 2 to nitrogen ratio under conditions of increased total gas pressure actually improves resilience to gas bubble trauma (Pleizier et al., 2020). This is because O 2 , as opposed to nitrogen, is consumed by aerobic metabolism, which leads to a lower total gas pressure in the tissues than would otherwise be experienced at a particular level of increased total gas pressure (Pleizier et al., 2020).…”
Section: The Influence Of Hyperoxia On Growth Performance and Gas Bubmentioning
confidence: 99%
“…This occurs when atmospheric gases mix with the water passing through the gates, air bubbles become entrained, and the bubbles dissolve into the water in the plunge pool at the base of the spillway. Fish tissues and blood can become supersaturated with TDGs, they can accumulate and come out of solution (i.e., nucleate) under conditions of sudden changes in temperature and pressure, which can result in the development of gas bubble trauma (GBT) (Bouck 1980, Weitkamp and Katz 1980, Pleizier et al 2020a. As a result of GBT, bubbles can form in the fins, skin, or behind the eyes, whereas more severe injuries such as bubbles forming in the blood or gills can cause mortality.…”
Section: Fish Injury and Mortalitymentioning
confidence: 99%
“…Injury and mortality resulting from GBT depends on the duration and the level of TDG exposure. In Rainbow Trout (Oncorhynchus mykiss), mortality rarely occurs from exposure to < 110% TDG, takes roughly 10 days to occur at 110%, and can be as rapid as 2 h at 140% (Pleizier et al 2020a).…”
Section: Fish Injury and Mortalitymentioning
confidence: 99%
See 2 more Smart Citations